The Story of N : A Social History of the Nitrogen Cycle and the Challenge of Sustainability - Gorman, Hugh S. (Hugh Scott), 1957- (Book collections on Project MUSE., 2013)
The Story of N analyzes the notion of sustainability from a fresh perspective, the integration of human activities with the biogeochemical cycling of nitrogen, and provides a supportive alternative to studying sustainability through the lens of climate change and the cycling of carbon. It is the first book to examine the social processes by which industrial societies learned to bypass a fundamental ecological limit and, later, began addressing the resulting concerns by establishing limits of t.